Description of two new species and new geographical records from the Neotropical region (Coleoptera, Cerambycidae) - Heffern, Daniel; Nearns, Eugenio H.; Santos-Silva, Antonio (Zootaxa, 2025)
Two new species of Onciderini are described: Oncideres anomala sp. nov., from Mexico; and Oncideres olanchana sp. nov., from Honduras. New geographical records and/or notes are provided for six species: Eudesmus posticalis Guérin-Méneville, 1844; Hesychotypa albofasciata Pérez-Flores & Nearns, 2021; Oncideres manauara Martins & Galileo, 1995; Oncideres quercus Skinner, 1905; Physopleurus rugosus (Gahan, 1894); and Tulcus picticornis (Bates, 1865).